A Kinetic Study of Aluminium(III) and Chromium(III) Adsorption by Silica Gel Chaetoceros calcitrans Biomass Immobilized on Silica Gel - Indah Raya; Narsito Narsito; Bambang Rusdiarso (Universitas Gadjah Mada, 2001)
The kinetics of aluminium(III) and chromium(III) adsorption in an adsorbent prepared by immobilization of Chaetoceros calcitrans biomass on silica ge has been investigated. The functional groups which were probable involved in the adsorption processes also identified. Experimentally, the adsorption was conducted by coloumn and batch method. In this work atomic adsorption spectrophotometric techniques was applied indirectly to determine of the metal ion adsorpted, and infra red spectroscopic technique was used for the identification of functional groups present in the adsorbent. The study included two parts of experiment, i.e. 1) the determination of rate of adsorption and 2) the determination of capacity and energy of adsorption. Results showed that the AI(III) and Cr(III) adsorption data fit quiet well with non linear kinetics model proposed by Langmuir-Hinshelwood giving a first order rate constant, (k1) of 8.65.10-3 min-1 for AI(III) and 9.92.10-4 min' for Cr(III) when the immobilized biomass used as the adsorbent in agreement with the activation energy calculation giving values of 1.184 kcal/mole for Al(111) and 1.877 kcal/mole for Cr (Ill). It was concluded that the adsorption of Al(III) and Cr(III) on Chaetoceros calcitrans immobilized and free Chaetoceros calcitrans adsorbents, may be classified as chemical adsorption, involving entalphi of adsorption in the range of 6-17 kcal/mole. And the infra red spectroscopic data indicated that the functional groups i.e.: carboxylate (-COO), hydroxyl (-OH) silanol (SI-OH), siloksil (SI-O-Si) and amine (NH2) are present in free Chaetoceros calcitrans biomass and silanol (Si-OH), siloksil (Si-O-Si), hydroxyl (-OH)and C-H metilene (-CH2) are present in immobilized biomass Chatoceros calcitrans, while only siloksil (Si-O-Si) and silanol (Si-OH) in silica gel.